(untitled) (Global Journal of Science Frontier Research, 2011)
Mathematical morphology examines the geometrical structure of an image by probing it with small patterns, called ’structuring elements’, of varying size and shape. This procedure results in nonlinear image operators which are suitable for exploring geometrical and topological structures. A series of such operators is applied to an image in order to make certain features more clear. Scale-space is an accepted and often used formalism in image processing and computer vision. Today, this formalism is so important because it makes the choice at what scale visual observations are to be made explicit. Fractal Geometry is a very new branch in Mathematics. An attempt to link Morphological operators and Fractals is made in this paper.